Analisis Dan Perancangan Data Warehouse Untuk Pengelolaan Stok Barang Pada Cv Aneka Artha Niaga - Septi Putri Azzahra; Yohanes Agung Apriyanto; Andri Wijaya (CV. ITTC INDONESIA, 2023)
CV Aneka Artha Niaga is a developing company which operates in the field of kassemergud vesmuving distributor. Distributor means an actor who distributes finished products from factory production in the form of packaged snacks and drinks to shops that have registered as customers. As a business that operates in the distribution sector, stock management is an important factor in the success of selling the products they offer. From availability to distribution to customers. The large amount of data that is managed makes it difficult for CV Aneka Artha Niaga to process data analysis and make decisions. This research aims to overcome existing problems at CV Aneka Artha Niaga by implementing a data warehouse with the ITL (Extract, Transform, Load) process. The method used is Kimball's nine steps. Data was collected through field observations, interviews, and the company's ERP system. The result of this research is the implementation of a data warehouse which can be the answer to the problems and information that CV Aneka Artha Niaga needs.